Highly crystalline SiCf/SiC composites produced by particle enhanced polymer impregnation and pyrolysis (PE-PIP) - Can Akaoglu; Junquan Lao; Kerui Wei; Philip J. Withers; Ping Xiao (Materials & Design)
Silicon carbide fiber (SiCf) reinforced/silicon carbide (SiC) matrix composites (SiCf/SiC) produced by polymer impregnation and pyrolysis (PIP) typically exhibit low density and crystallinity due to the formation of a SiCxOy amorphous matrix. This compromises the mechanical and thermal properties of the composites. Here, a particle enhanced PIP (PE-PIP) method is proposed whereby fine silicon carbide particles (SiCp) containing amorphous silica (SiO2) layer are incorporated into the liquid poly (carbosilane) (PCS)-based precursor. The addition of SiCp improved the bulk density and decreased the open porosity of the composites compared to conventional PIP processing. After heat treatment at 1400 °C for 8 h, the true density of the composites was enhanced further with a reduced carbon content via the carbothermal reactions between SiO2 and the excess carbon present in the PIP matrix. However, the bulk density reduced due to increased open porosity which could be sealed by subsequent processing. This novel processing approach has the potential to deliver high density, high crystallinity SiCf/SiC with low carbon content by PIP at low temperature (1400 °C).